The development of public relations and protocol teaching material based on the 2013 Curriculum in vocational school - Andre Noevi Rahmanto; Arif Wahyu Wirawan (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2017)
This research aimed to describe the development of public relations and protocol office administration teaching material based on the 2013 curriculum in Vocational School (thereafter called SMK). This study was a Research & Development (R & D) using Borg & Gall's model. This research involved Public Vocational School with Office Administration Specialty in Ex-Surakarta Residency area. Technique of collecting data used was interview with informants related to Office Administration teaching material. Meanwhile for the trial, technique of collecting data used was questionnaire survey distributed to teachers and students. The effectiveness of data collection was tested using test. Technique of analyzing data used was mix method, the combination of qualitative and quantitative methods. The result of analysis using 2-way anava obtained Fstatistic value of 0.829 in Vocational School with probability (sig.) value of 0.438. F test results are seen in the anova table in the sig column. Experiment group had an improvement of learning outcome better than the control one with the mean increase of 4.5 while control group had mean score of 2.3. Thus, it could be concluded that public relations and protocol teaching material based on the 2013 curriculum was feasible to use in Vocational School (SMK).